'Because of the circumstances, we cannot develop our role': Norwegian community pharmacists' perceived responsibility in role development. (30th October 2014) - Svensberg, Karin; Kälvemark Sporrong, Sofia; Håkonsen, Helle; Toverud, Else-Lydia
Abstract: Objective: The development of more patient-centred care is not always visible in community pharmacies. The aim of this study was to explore Norwegian pharmacists' motivation and perceived responsibility regarding role development and involvement in patient-centred care. Methods: A semi-structured interview guide was developed. Four focus group interviews were conducted with a heterogeneous sample of 21 community pharmacists and transcribed verbatim. An inductive analysis was performed, supplemented with an agent perspective. Key findings: Two main categories and nine subcategories were identified, with the main categories being 'reality vs. vision' and the overall 'agent' category. A gap was found between what the pharmacists said they were doing in their day-to-day work and what they expressed as their ideal tasks in the pharmacy. The pharmacists seem to transfer the need for their role as active medicine experts in patient-centred care to other agents such as authorities and pharmacy chains. Conclusions: There is a gap between what the Norwegian community pharmacists express as their vision and current practice. The identified agent relationships appear to hamper the pharmacists' perceived ability to be active and take full responsibility in their role development and further implementation of patient-centred care. Adopting a fairly inactive position when it comes to increasing patient-centred care might be a result of a traditional product-focused pharmacy culture.